2010
DOI: 10.4261/1305-3825.dir.3141-09.1
|View full text |Cite
|
Sign up to set email alerts
|

Popliteal artery branching patterns detected by digital substraction angiography

Abstract: Awareness of the anatomical variability determined by embryonic vascular development is important for radiologists and surgeons. Popliteal arterial variation may have clinical implications for vascular grafting, direct surgical repair, transluminal angioplasty, or embolectomy. Moreover, differentiating occlusion or arterial injury from variation depends on the clinician's knowledge of variations (1-10). Therefore, we aim to describe popliteal arterial variations. Materials and methodsThe femoral angiograms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
5
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 10 publications
4
33
5
2
Order By: Relevance
“…The proximal part then regresses. Primitive middle and distal segments of the sciatic artery persists to form definitive popliteal and peroneal arteries [9].…”
Section: 1embryological Significancementioning
confidence: 99%
“…The proximal part then regresses. Primitive middle and distal segments of the sciatic artery persists to form definitive popliteal and peroneal arteries [9].…”
Section: 1embryological Significancementioning
confidence: 99%
“…Its frequency in the literature ranges from 6.0% (Davies et al, 1989) [22] to 1.5% (Kil & Jung, 2009) [8]. Not even studies with a lower prevalence of the pattern IA presented values as expressive as this study, such as Mavili et al in 2011, which found 84.4% for the common pattern and 5.4% for trifurcation [9]. Probably, this is due to the patterns of category II of Kim et al [6], high tibiofibular division of the popliteal artery branch, which is representative in the literature [6,8,9,14,16,23].…”
Section: Methodsmentioning
confidence: 68%
“…Not even studies with a lower prevalence of the pattern IA presented values as expressive as this study, such as Mavili et al in 2011, which found 84.4% for the common pattern and 5.4% for trifurcation [9]. Probably, this is due to the patterns of category II of Kim et al [6], high tibiofibular division of the popliteal artery branch, which is representative in the literature [6,8,9,14,16,23]. In some cases, it exceeds trifurcation, 4.5% for the high division and 3.2% for trifurcation (Day & Orme, 2006) [10].…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…Up to 75 variations of normal can occur [12], including branches above the knee joint, and hypoplastic branches. This combined with muscular entrapment will affect the pattern and severity of symptoms, and subsequent treatment options [12,13]. Therefore knowledge of the path of the popliteal artery and its branches is essential.…”
Section: Arterial Variation In the Popliteal Fossamentioning
confidence: 99%